Optimization of Process Parameters and Microstructure of CoCrFeNiTiAl High-Performance High-Entropy Alloy Coating - Bingchun Jiang; Zhu Huang; Cunyu Liu; Huipeng Wang; Fengyuan Shu; Yuncai Zhao; Heping Lei (Metals)
CoCrFeNiTiAl high-entropy alloy coatings have been prepared by laser cladding technology based on response surface methodology (RSM). The results show that the effects of laser power, cladding speed, and pulse width on the dilution rate and microhardness of the high-entropy alloy coatings are investigated. Among the single-factor results, the laser power has the most significant effect on the properties of high-entropy alloy coatings, followed by the cladding speed, while the pulse width has no significant effect. In the interaction term analysis, the interaction term of laser power and pulse width has a remarkable effect on both output responses, whereas the interaction term of pulse width and cladding speed only has a considerable effect on microhardness, while the interaction term of laser power and cladding speed has an insignificant effect on both output responses. The optimum parameters for the preparation of high-performance high-entropy alloy coatings are found at laser power P = 676.73 W, cladding speed V = 5 mm/s, and pulse width P0 = 9 ms. The microstructures of the high-entropy alloy coating prepared with optimal process parameters have been characterized, which show that the metallurgical bonding between the cladding layer and the substrate is strong and without obvious defects such as porosity and cracks.